PEMAHAMAN NILAI-NILAI PENDIDIKAN KARAKTER ISLAMI DALAM CERITA ANAK OLEH GURU MADRASAH IBTIDAIYAH (MI) DAN SD SE KECAMATAN SUKODADI UNTUK PENINGKATAN PEMBELAJARAN AGAMA ISLAM (TINJAUN PRAGMATIK RESEPTIF) - Ernaningsih Ernaningsih; Luluk Faridah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2018)
This study aims to describe and explain: (1) understanding of Islamic character education values ​​contained in children's stories by teachers, and (2) contextualization of Islamic character education values ​​contained in the story children as an improvement in religious learning models. The method used in this study is qualitative descriptive with the Pragmatic Receptive approach. The data in this study are data about (1) Understanding the Islamic character education values ​​contained in children's stories, and (2) contextualization of character education values ​​contained in the story as a model of Islamic learning. Data sources are obtained from documentation and interviews. The data collection techniques are carried out with documentation and interviews. Data analysis techniques use interactive techniques. The findings of the study can be described include: (1) Understanding the value of Islamic character education in children's stories, Akhlak have faith, are grateful, morality is devoted to both parents, and teachers, healthy and clean, mutual cooperation and virtuous character are not arrogant, (2) contextualization of Islamic character education values ​​contained in children's stories as an enhancement of the Islamic learning model.